Preparation of pure Silica Oxide (Sio2) and Zeolite Y from rice husk as an ion exchanger for emergency water treatment system using in flood affected area - Rahman, Md. Mokhlesur; M. B., Awang; Yusof, Alias Mohd (Trans Tech Publications Ltd., Switzerland, 2012)
Thermal and acid wash treatment of rice husk has been conducted 550 to 600 0C in air atmosphere and chemical treatments consisted of acid, H2SO4. Purity, pore size distribution, FT-IR and SEM micrographs of treated and non-treated samples are presented. In this study the acid treated rice husk ash was used as SiO2 source in the preparation of zeolite Y, a medium siliceous zeolite used as an ion exchanger in water treatment process. Obtained zeolite Y, BET Surface area 621.18 square meters per gram, pore volume is 0.33 cubic centimeters per gram and its average pore diameter is 21.222 Å. Ion-exchange capacities were tested through a column packed in zeolite Y by the artificially polluted water filtration, filtrate was analysed by ICP-MS and elements (As,Ba, Ca, Cd, Co, Cr, Bi, Be, Pb Ni etc.) in filtered waters was found in negative amounts. Zeolite Y is found a highly efficient ion-exchange material. So, mini water filtering system is a good for water treatment, even water is highly polluted by toxic elements.